Rescue story [compact disc] - Williams, Zach; Williams, Zach (Essential Records, 2019)
Following his Grammy Award winning album, Chain Breaker, Zach Williams is back with his highly anticipated sophomore album. One of the songs, There Was Jesus, features country music legend Dolly Parton.